2008
DOI: 10.1007/s10340-008-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of planting date on the relationship between populations of Frankliniella flower thrips and predatory bug Orius niger in cotton

Abstract: The influence of three planting dates [midMarch (early-planted), 15 April-15 May (normal-or timely planted) and mid-June (late-planted)] of cotton variety SG 125 on the relationship between populations of Frankliniella flower thrips (Thysanoptera: Thripidae) and the predatory bug, Orius niger (Wolff) (Hemiptera: Anthocoridae) were investigated in Adana province in the Eastern Mediterranean region of Turkey in 2003 and 2004. To facilitate emergences of cotton seedlings in early-plantings, cotton rows were mulch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…There are also other important biotic and abiotic factors that can aVect the abundance of these predators. Atakan and Gencer (2008) concluded that the populations of O. niger were more abundant in normalplanted cotton Welds and its population density signiWcantly correlated with the Frankliniella occidentalis (Pergande) population. With regard to predator-thrip interactions, they suggested that O. niger might be an eYcient biological control agent to regulate western Xower thrips, especially in normal-planted cotton.…”
Section: Discussionmentioning
confidence: 97%
“…There are also other important biotic and abiotic factors that can aVect the abundance of these predators. Atakan and Gencer (2008) concluded that the populations of O. niger were more abundant in normalplanted cotton Welds and its population density signiWcantly correlated with the Frankliniella occidentalis (Pergande) population. With regard to predator-thrip interactions, they suggested that O. niger might be an eYcient biological control agent to regulate western Xower thrips, especially in normal-planted cotton.…”
Section: Discussionmentioning
confidence: 97%
“…(Hemiptera: Anthocoridae) are often considered important natural enemies of thrips (Riudavets et al 1995). In Turkey, Orius niger (Wolff) effectively suppresses the Frankliniella flower thrips in cotton fields in the Çukurova region that are not treated with insecticides (Atakan 2006;Atakan and Gençer 2008). Orius spp.…”
Section: Introductionmentioning
confidence: 99%
“…Although in general, Orius densities were relatively greater in late-sown cotton, there were significant and positive relationship between thrips and Orius mean numbers only in early-sown cotton (March 1 or March 5 sowing regime). In previous studies various researchers reported that, populations of O. niger significantly and positively correlated with F. occidentalis population in normal-planted (lateApril or early-May) cotton (Atakan, 2006;Atakan & Gencer, 2008). These differences between studies may be because of different sowing date regimes.…”
Section: Discussionmentioning
confidence: 94%
“…Abundance of coccinellid predator Hippodomia (Adonia), variegata (Goeze) and Orius were appreantly related to cotton sowing date and to the abundance of cotton leafhoppers; fields which were cultivated in early time, proned to get greater densities of predators (Prasifka et al, 2004). In the same ecological area (Çukurova Region), Atakan & Gencer (2008) investigated population densities of the flower thrips in early (Late-March), normal or timely-(Mid-April or Mid-May) and late (June) sown cotton. These researchers reported reduction in the population of insect pest and natural enemies as well as thrips and Orius in early March sown cotton by using mulchsowing technique.…”
Section: Introductionmentioning
confidence: 97%